Prescribing the Dharma : psychotherapists, Buddhist traditions, and defining religion - Helderman, Ira (The University of North Carolina Press, 2019)
"Interest in the psychotherapeutic capacity of Buddhist teachings and practices has captured the popular imagination. News media regularly post stories about the neuropsychological study of Buddhist meditative states and applications of "mindfulness" practices in diverse settings including corporate business headquarters, the U.S. military, and university health services. However, Ira Helderman shows, for well over a century investigators, stretching back to James, Jung, and others fascinated by the psychology of religion, have studied the psychological dimensions of Buddhist doctrine. They have influenced the mental health field and shaped common understandings of "Buddhism" for many Americans. Prescribing the Dharma is the first book to focus on psychotherapists themselves. Drawing on extensive fieldwork and in-depth interviews with many clinicians who have been formative in the use of Buddhist ideas and concepts, Helderman looks at how the key categories of 'religion' and 'secularism' operate for such caregivers"--